Learning Strategies at SMP Muhammadiyah 5 Surabaya in Learning Al Islam Kemuhammadiyah during the Covid-19 Pandemic - Nurul Kholifah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study is to provide information about Online Learning Using Information Search Methods for Al-Islamic kemuhammadiyahan Subjects in Muhammadiyah 5 Junior High School Surabaya in Covid-19 Conditions. This research is class ified as a descriptive qualitative research. This study tries to explain online learning by using the Information Search Method of Al-Islamic kemuhammadiyahan Subjects in SMP Muhammadiyah 5 Surabaya in Covid-19 Conditions. Primary data sources are interviews conducted through Google Form. The source of supporting data is the theory of figures, and relevant research written by other authors. This finding shows that the use of the Information Search method when online learning in Al-Islamic kemuhammadiyahan subjects can be applied in the midst of current learning problems with the situation of Indonesia that is affected by Covid-19. Online learning is an educational innovation that uses internet media without any limitations on space and time in carrying out the learning process. Online learning is a solution to overcome the educational problems caused by the current Covid-19 pandemic.